Geographic Variation in Outcomes After Burn Injury: A Burn Model System National Database Study. Issue 6 (June 2020) - Espinoza, Leda F.; Friedstat, Jonathan; Faoro, Nicholas; Chang, Philip H.; McMullen, Kara A.; Simko, Laura C.; Esselman, Peter; Holavanahalli, Radha; Ryan, Colleen M.; Schneider, Jeffrey C.
Abstract : Background: Geography is an important yet underexplored factor that may influence the care and outcomes of burn survivors. This study aims to examine the impact of geography on physical and psychosocial function after burn injury. Methods: Data from the Burn Model Systems National Database (1997–2015) were analyzed. Individuals 18 years and older who were alive at discharge were included. Physical and psychosocial functions were assessed at 6, 12, and 24 months postinjury using the following patient-reported outcome measures: Community Integration Questionnaire, Physical Composite Scale and Mental Composite Scale of the 12-Item Short Form Health Survey, Satisfaction with Appearance Scale, and Satisfaction with Life Scale. Descriptive statistics were generated for demographic and medical data, and mixed regression models were used to assess the impact of geography on long-term outcomes. Results: The study included 469 burn survivors from the Centers for Medicare and Medicaid Services regions 10, 31 from region 8, 477 from region 6, 267 from region 3, and 41 from region 1. Participants differed significantly by region in terms of race/ethnicity, burn size, burn etiology, and acute care length of stay ( P < 0.001). In adjusted mixed model regression analyses, scores of all 5 evaluated outcome measures were found to differ significantly by region ( P < 0.05). Conclusions: Several long-term physical and psychosocial outcomes of burn survivors vary significantly by region. This variation is not completely explained by differences in population characteristics. Understanding these geographical differences may improve care for burn survivors and inform future policy and resource allocation.